2023
DOI: 10.1371/journal.pone.0294776
|View full text |Cite
|
Sign up to set email alerts
|

Comparative chromosome painting in three Pelecaniformes species (Aves): Exploring the role of macro and microchromosome fusions in karyotypic evolution

Igor Chamon Assumpção Seligmann,
Ivanete de Oliveira Furo,
Michelly da Silva dos Santos
et al.

Abstract: Pelecaniformes is an order of waterbirds that exhibit diverse and distinct morphologies. Ibis, heron, pelican, hammerkop, and shoebill are included within the order. Despite their fascinating features, the phylogenetic relationships among the families within Pelecaniformes remain uncertain and pose challenges due to their complex evolutionary history. Their karyotypic evolution is another little-known aspect. Therefore, to shed light on the chromosomal rearrangements that have occurred during the evolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The main rearrangements were fusion events, including macro-and microchromosome. In Syrigma sibilatrix, the GGA8, GGA9, and GGA10 chromosome paints hybridized to the long arms of biarmed macrochromosomes, also indicating fusions with microchromosomes [100]. Although BOE and chicken (GGA) microchromosome paints do not allow for the identification of the exact microchromosome involved in the fusion events, these studies indicated that fusion events involving these tiny chromosomes are nonetheless frequent among Pelecaniformes.…”
Section: Pelecaniformesmentioning
confidence: 89%
See 1 more Smart Citation
“…The main rearrangements were fusion events, including macro-and microchromosome. In Syrigma sibilatrix, the GGA8, GGA9, and GGA10 chromosome paints hybridized to the long arms of biarmed macrochromosomes, also indicating fusions with microchromosomes [100]. Although BOE and chicken (GGA) microchromosome paints do not allow for the identification of the exact microchromosome involved in the fusion events, these studies indicated that fusion events involving these tiny chromosomes are nonetheless frequent among Pelecaniformes.…”
Section: Pelecaniformesmentioning
confidence: 89%
“…Molecular cytogenetics is still scarce in this order; however, recent studies using chromosome painting with chicken and/or stone curlew (B. oedicnemus, BOE) paints indicated that the karyotype of Pelecaniformes is reorganized, similar to that of the parrots and falcons [99,100]. The stone curlew chromosome painting in three Pelecaniformes species (Ardea cinerea, Egretta garzetta, and Nipponia nippon) indicated that different chromosome rearrangements occur in different Pelecaniformes lineages [99].…”
Section: Pelecaniformesmentioning
confidence: 99%